ON THE PRACTICE OF KEEPING AND REARING BAMBOO RATS (RODENTIA, SPALACIDAE, RHIZOMYS) IN VIETNAM - Dinh, The Dung; A. E, Balakirev (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Bamboo rats are members of the subfamily Rhizomiinae, of the family Spalacidae. These animals are widely distributed in Indonesia, Malaysia, Thailand, Myanmar, Laos, Vietnam and China. Due to their larger size compared to other rodents, in recent years they have been bred in captivity and have brought a certain economic value. With the survey results of 16 bamboo rat farms in 2 Northern provinces and 3 Southern ones, a preliminary overview of the current situation with bamboo rats production in Vietnam presented. More than 1000 individuals were surveyed and only two species of bamboo rats have been found in captivity, exactly R. pruinosus and R. sumatrensis. R. sinensis was not recorded, although this species quite common in the north. Bamboo rats are usually kept in cages made of ceramic bricks about 50 cm high and 0.25 - 0.8 m wide. Each cage usually contains 1 adult male or 1 female, sometimes both male and female are seen in the case with juveniles in the same flock. The survival rate of young bamboo rats is very high, only 3-5% of the total herd dies before reaching the weight of 300g. The source of food depends on the locality, but the main food is bamboo, sugarcane, cane or bran. The average annual income may vary from 30-50 for small farms to 100-120 million VND for large farms.